Novel ''flow injection'' channel flow cell for the investigation of processes at solid-liquid interfaces .2. Experiment - Gooding, J; Brennan, C; Atherton, J; Coles, B; Compton, R (1997)
A novel "flow injection" channel flow cell, which enables the study of transient phenomena at diverse solid/liquid interfaces, is described. The cell is comprised of a rectangular duct through which solution flows under laminar flow conditions. In one wall of the duct is embedded the solid substrate of interest, and directly adjacent to this is the detector electrode. The solution species of interest enters the primary channel flow system from a secondary flow upstream of the solid substrate, located in the opposite wall, without seriously disrupting the well-defined flow profile in the former. The amount of the species injected, and the extent of any reaction with the solid substrate, is determined at the downstream detector electrode. Thus, the flow injection channel flow cell is similar to a double channel electrode but where the injection slit performs the function of the generator electrode (introducing a reactant species into the channel at a precise time). The rise time of the transient was comparable to a double channel electrode of analogous geometry (in which the generator electrode mimics the injection slit), and the detector current dies away to zero almost instantly once the injection is turned off. The variation in steady-state current with flow rate was shown to agree excellently with a theoretical description of the cell1 without the need for any adjustable parameters. The cell was successfully used to monitor the reaction between the dye orange G and virgin cotton cloth.